Plantas de cobertura e qualidade química e física de Latossolo Vermelho distrófico sob plantio direto - Da Silva, Mariana Pina (2017)
The study aimed to evaluate the influence of species of cover crops on chemical and physical soil properties. The survey was conducted during the winter of 2010 and 2011 in Selvíria, Mato Grosso do Sul State, Brazil. The experimental design was a randomized block in a split plot with four replicates. The plots consisted of: millet, sun hemp, pea, velvet bean, millet + pigeon pea, millet and millet + crotalaria, and mucuna fallow. The subplots were represented by the absence of phosphate fertilizers and P2O5rates (60, 90 and 120 kg ha-1) in the form of monoammonium phosphate (MAP). The subplots that have not received phosphate fertilizer chemical and physical soil properties were analyzed. The species used as cover caused changes in the chemical and physical properties of the soil. The soil maintained with millet + black mucuna presented the highest values of P and Ca, on millet higher values of OM, pigeon higher values of K, and those under the consortium millet + pigeon had higher concentrations of Mg. The soil maintained with millet Presented lower values of density and higher values of porosity.